Does cannabis use increase anxiety disorders? A literature review. Issue 1 (January 2020) - Shalit, Nadav; Lev-Ran, Shaul
Abstract : Purpose of review: Cannabis is widely used worldwide and cannabis use disorders are highly comorbid with anxiety disorders. In this review, we consider the recent literature on the effects of cannabis on the incidence, course, and treatment outcomes of anxiety disorders. Recent findings: Although cannabis use is mostly found to be associated with increased incidence of anxiety disorders, these findings are generally not sustained in adjusted analyses controlling for multiple confounders. There are some equivocal data suggesting higher risk for anxiety disorders among heavy cannabis users. The scarce data available indicates no clear effect of cannabis use on the course and treatment outcomes of anxiety disorders. Summary: Further research is needed focusing on trajectories of cannabis-induced acute anxiety, effects of cannabis use on treatment outcomes in anxiety disorders, and common genetic factors. Future epidemiological studies should utilize more precise measures of cannabis use and address several confounding factors which may affect the association between cannabis use and anxiety disorders.